Pengembangan Hypothetical Learning Trajectory (HLT) pada Pembelajaran Statistika untuk Meningkatkan Pemahaman Konsep Siswa - Tri Putri Utami; Noviyanti Noviyanti; Nurul Asma (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2026)
This study aims to develop a Hypothetical Learning Trajectory (HLT) in statistics learning that is valid, practical, and effective in improving students’ conceptual understanding. This research employs a Research and Development method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this study were eighth-grade students at SMP Negeri 1 Peureulak. Data were collected through conceptual understanding tests, observations, interviews, and documentation. The research instruments included expert validation sheets, pretest and posttest items, and observation sheets of student activities. The results indicate that the developed HLT is categorized as valid based on expert judgment. The implementation of HLT in learning shows an improvement in students’ conceptual understanding, as indicated by the increase in the average score from 58.20 in the pretest to 82.45 in the posttest, with a gain score of 0.58 categorized as moderate. In addition, there was an increase in students’ active engagement during the learning process, particularly in discussions and data interpretation. The HLT also assists teachers in designing more systematic instruction and anticipating students’ misconceptions. Therefore, the developed HLT is practical and effective in improving students’ conceptual understanding in statistics and can serve as an alternative innovative instructional design.